The Effect of Deductive-Inductive Learning Approach on Creative Thinking Ability and Learning Motivation - Sinaga, Nurul Afni; Ningtiyas, Fitri Ayu; Mahmuzah, Rifaatul; Zahara, Yulia; Fatwa, Islami (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2023)
Mathematics learning can have an impact on the development of one's mindset in the learning environment. This process is obtained through teacher innovation which provides learning with various methods and approaches that are in line with what will be taught. Inductive-deductive is an approach that can help students' creative thinking processes and increase learning motivation. For this reason, this study wanted to see how effective and influential this approach is on the ability to think creatively and motivation to learn. The method used is a significant test using one sample t-test and one paired sample t-test. The results obtained are t-count values of 2.09 and 10.66 for the inductive-deductive class and -0.848 and -0.94 for the conventional class where the t-table value is 1.684. Whereas to see the effect of the approach obtained values of 6.149 and 6.344 with a t-table of 1.960. The value that is greater than the t-table states that the class is effective and has influence, so it can be concluded that the inductive-deductive approach is effective for critical thinking skills and learning motivation, while conventional classes are not used effectively. The inductive-deductive approach also influences students' creative thinking abilities and learning motivation.